The Odae chinŏn (Five Great Mantras) and Dhāraṇī Collections in Premodern Korea - Richard D. McBride (Religions, 2022)
The Five Great Mantras (Odae chinŏn) is one of the most widely circulated collections of Buddhist dhāraṇīs in premodern Korea, having been published or existing in several variant editions during the Chosŏn period (1392–1910). The title refers to the following dhāraṇīs: (1) “The Forty-Two Mantras of the Bodhisattva Avalokiteśvara,” (2) Nīlakaṇṭha-dhāraṇī, (3) Mahāpratisarā-dhāraṇī, (4) Buddhoṣṇīṣa-dhāraṇī, and (5) Uṣṇīṣavijaya-dhāraṇī. Another spell, “The Basic Dhāraṇī of the Bodhisattva Avalokiteśvara,” was also added, so there are a total of six dhāraṇīs contained in the book. Although most scholarship has hitherto understood the Five Great Mantras to date from the late fifteenth century, when editions with transcriptions of the dhāraṇīs in the Korean script appeared in trilingual format along with Siddhaṃ and Sinitic transliterations, due to the patronage of Queen Insu (1437–1508) and the linguistic ability of the monk Hakcho (fl. 1464–1520), some evidence has come to light suggesting that the Five Great Mantras was initially published as early as the mid-fourteenth century in the late Koryŏ period (918–1392). This essay provides a detailed analysis of the components that appear in the Five Great Mantras by analyzing six variant editions of the text dating from the Chosŏn period, including Brief Transcriptions of Efficacious Resonance (Yŏnghŏm yakch’o) in Sinitic and Korean vernacular translation. The Five Great Mantras demonstrates the significance of non-canonical materials in the Korean Buddhist tradition and suggests a fruitful avenue for study of similar woodblock prints and manuscripts in the Sinitic Buddhist tradition.